Philosophical Perspective of the Community Counseling Services to Facilitate Adolescents’ Development in Indonesia: A Systematic Review - Lestari, Rizqi; Purwanta, Edi; Rukiyati, Rukiyati (Indonesian Journal of Educational Counseling, 2025)
Guidance and counseling have ontological, epistemological, and axiological foundations that are the basis for the implementation of services both in schools and outside schools. As one of the services in guidance and counseling, community counse1ling services cannot be separated from the underlying philosophical perspective, especially tp facilitate adolescents' development. This research aims to analyze the philosophical perspective of community counselling implementation to facilitate the development of adolescents in Indonesia. The research method used is a systematic literature review. The data collection technique was carried out by searching for articles on Google scholar using the keywords "community counselling" and "adolescent" in English and Indonesian. The data analysis techniques used the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) model and resulted in 12 of 200 research articles that could be analyzed. The analysis results show that implementation community counselling to facilitate adolescent development has not been widely implemented in Indonesia. There is a distinctive philosophical basis in all the articles analyzed. From an ontological perspective, community counseling tends to target marginalized groups such as former drug addicts, children with special needs, and the elderly. Meanwhile, an epistemological perspective shows that knowledge and truth in community counseling are still being formed through various subjective observations and experiences. The idea of integrating religion and culture in several articles shows that community counseling services have an axiological basis with a strong multicultural spirit. Further research is expected to be able to explore more deeply regarding each philosophical basis in community counseling services.